2014
DOI: 10.1007/s00221-014-3960-7
|View full text |Cite
|
Sign up to set email alerts
|

Auditory deprivation affects biases of visuospatial attention as measured by line bisection

Abstract: In this study, we investigated whether early deafness affects the typical pattern of hemispheric lateralization [i.e., right hemisphere (RH) dominance] in the control of spatial attention. To this aim, deaf signers, deaf non-signers, hearing signers, and hearing non-signers were required to bisect a series of centrally presented visual lines. The directional bisection bias was found to be significantly different between hearing and deaf participants, irrespective of sign language use. Hearing participants (bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
1
23
2
Order By: Relevance
“…Moreover, low pitch listening produced leftward bias, whereas high pitch listening produced rightward bias both in musicians (Lega et al, 2014 ) and non-musicians (Ishihara et al, 2013 ). Consistently with the idea that music listening can produce perceptual and cognitive effects beyond the auditory modality, a very recent study indicated that while deaf participants showed a tendency to deviate rightward, normally-hearing subjects displayed the typical leftward pseudoneglect (Cattaneo et al, 2014 ). The present results suggest that not only a long-lasting musical training (as occurring in musicians) or the absence of auditory perception (as occurring in deafness) modulate visuo-spatial attention, but also a few minutes of music listening ( as long as combined with the appropriate cerebellar pre-conditioning) modulate spatial attention inducing a rightward deviation closer to the real center.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, low pitch listening produced leftward bias, whereas high pitch listening produced rightward bias both in musicians (Lega et al, 2014 ) and non-musicians (Ishihara et al, 2013 ). Consistently with the idea that music listening can produce perceptual and cognitive effects beyond the auditory modality, a very recent study indicated that while deaf participants showed a tendency to deviate rightward, normally-hearing subjects displayed the typical leftward pseudoneglect (Cattaneo et al, 2014 ). The present results suggest that not only a long-lasting musical training (as occurring in musicians) or the absence of auditory perception (as occurring in deafness) modulate visuo-spatial attention, but also a few minutes of music listening ( as long as combined with the appropriate cerebellar pre-conditioning) modulate spatial attention inducing a rightward deviation closer to the real center.…”
Section: Discussionmentioning
confidence: 66%
“…The link between music listening and spatial abilities has been previously described (Stewart and Walsh, 2007 ; Cattaneo et al, 2014 ; Lega et al, 2014 ). In musically untrained subjects, listening to sounds of different pitch prompts mental spatial representations (Rusconi et al, 2006 ; Lidji et al, 2007 ).…”
Section: Introductionmentioning
confidence: 79%
“…In this sense, goal-directed movements towards the objects, based in the egocentric frame of reference, are slower than in NH [41]. In addition, auditory deprivation affects brain spatial organization; thus, in contrast with NH children, who have shown right hemisphere activation for spatial attention, an atypical bilateral or left hemisphere activation has been seen in HI children [40,42]. Furthermore, spatial cognition is promoted by an expertise in spatial language [43] and language absence results in poor performance on non-linguistic spatial tasks, particularly those combining different spatial representations [44].…”
Section: Introductionmentioning
confidence: 99%
“…Neville and colleagues proposed that greater recruitment of right hemisphere would be related to the visual-spatial characteristics of sign language. However, recent results suggest a reduction of hemispheric lateralization in a spatial attention task (Cattaneo et al, 2014). A shift of hemispheric lateralization during the detection of motion has also been demonstrated, deaf subjects showing a left hemisphere advantage, whereas hearing subjects showed a right hemisphere advantage (Bosworth and Dobkins, 1999; Bavelier et al, 2001; Bosworth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%